Effective limitation of line fault currents by means of the series-connected VSC-based facts devices - Vasquez-Arnez,R.L. (2006)
In this paper, the nearly instantaneous response of the series-connected VSC-based FACTS controllers when used to limit possible fault currents in a compensated line, will be presented. The effectiveness of both FACTS controllers (SSSC and UPFC) towards this system condition was investigated exploring the series voltage effect upon the line. Moreover, it will be shown that the UPFC shunt converter can also contribute to the reduction of such fault currents. The short-circuit current limitation strategy presented herein showed that aside of the power flow control and voltage support commonly carried out by the SSSC and the UPFC, they could also perform this additional functionality, thus offering a useful tool for the protection of the line in which these devices are installed.